Social Constructivism Based Project Based Learning in Senior High School Mathematics Education a Systematic Review - Ni Putu Sri Dianawati; I Gusti Putu Sudiarta; I Gede Suweken; I Nengah Suparta (Journal of Education and Teaching Learning, 2026)
This study aims to systematically review the implementation of social constructivism-based Project-Based Learning (PjBL) in mathematics education at the senior high school level over the past five years. The review focuses on the forms of PjBL implementation, types of projects, characteristics of student products, project authenticity, meaningfulness, relevance to classroom time constraints, and proposed solutions. A Systematic Literature Review (SLR) method was employed by analyzing twenty-two articles retrieved from Google Scholar, DOAJ, ERIC, and SINTA databases. The article selection process followed the PRISMA framework, including identification, screening, eligibility, and inclusion stages, and the data were analyzed using a thematic approach. The findings indicate that PjBL generally aligns with social constructivist principles through collaborative activities and social interaction. However, most projects remain dominated by academic and symbolic products, such as reports and presentations, with authenticity levels categorized as low to moderate. Furthermore, limited instructional time and teachers' readiness emerge as major challenges. This review highlights a significant research gap in developing authentic and meaningful mathematics projects that support deep learning and the achievement of advanced-level competencies, providing a novel epistemological perspective on how social constructivism is practically translated into project designs.